Induction, biochemical trait and phytochemical screening of calluses of Amburana cearensis (Allemão) A.C. Smith (Acta Scientiarum. Biological Sciences, 2020)
Amburana cearensis is an arboreal legume of the Fabaceae family, with high phytotherapic and medicinal potential due the presence of secondary metabolites. The objective of this study was to evaluate the effect of 2,4-dichlorophenoxyacetic acid (2,4-D) and 4-amino-2,5,6- trichloro-2-pyridinecarboxylic acid (picloram) on the in vitro induction of callogenesis of A. cearensis and analyze the biochemical and phytochemical potential of these calluses. For callus induction, leaf and cotyledon segments were used as explants, which were inoculated in woody plant medium (WPM) supplemented with different concentrations of 2,4-D (0, 5, 10, 20, 40 Î¼M) or picloram (0, 5, 10, 20, 40, 80 Î¼M). The callus growth curve was estimated based on fresh weight, measured at 7-day intervals until 28 days after inoculation. The calluses were analyzed by biochemical tests to quantify the reducing sugars and total proteins. Phytochemical screening and high-performance liquid chromatography were performed to establish the phytochemical profile of extracts from calluses. The concentrations of 21.94 Î¼M and 26.46 Î¼M of 2,4-D induced the greatest formation of compact and friable calluses from the leaf and cotyledon segments, respectively. The growth curve had two distinct phases (lag and exponential) for both types of calluses evaluated. The maximum levels of reducing sugars and total proteins in the calluses from leaf and cotyledon segments were obtained on the day of inoculation and after 28 days of cultivation, respectively. The results of the phytochemical analysis identified the presence of coumarin in all the extracts evaluated, this secondary metabolite has high pharmacological potential.